De encurralados pelos parques a vazanteiros em movimento: as reivindicações territoriais das comunidades vazanteiras de Pau Preto, Pau de Légua e Quilombo da Lapinha no campo ambiental - Felisa Cancado Anaya (2012)
The subjects of this thesis are the processes that allowed the construction of a specific social and political movement of territorial claiming in the north of Minas Gerais state, denominated by these actors as Vazanteiros em Movimento (Riverines in Movement). Such movement is constituted by the riverine communities of Pau Preto, Pau de Légua and Quilombo da Lapinha and emerged after their expropriation and enclosure by the creation of conservation units of restricted use (CURUs) along their traditional territories. Thus, the creation of three state parks (Verde Grande, Lagoa do Cajueiro and Mata Seca) as environmental compensation to the expansion of the irrigated perimeter of Jaíba had evidenced the contradictions of the environmental conservation policies. Such policies are driven by the economic rationality of the capitalist system and generated social-environmental conflicts that lead these communities to self-organization and political articulation to defend their territories. In this context, such processes of political construction and mobilization are analyzed, revealing the participation of regional social entities that contributed to the self-affirmation of the identity of the Vazanteiros communities, to the exchange of experiences on social struggles involving other collective organizations in the region, and to the approximation of distinct institutional and civilian stakeholders. All these factors allowed the Vazanteiros em Movimento to move from the condition of corralled by parks and incorporate cultural and technical capital to support their territorial claims. In this perspective, the appropriation of the discourse and juridical instruments peculiar to the environmental arena contributed to the environmentalization of their social struggles. This process opened the opportunity for the Vazanteiros em Movimento to dispute, in this arena, the access to alternative projects of sustainability and nature conservation that are associated to their traditions and livelihood conceptions.